(untitled) (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2011)
The purpose of the study was to explore the perceptions of Chinhoyi University of Technology employees about the possibility of using the Human Factor approach as a tool of analysis in enhancing connectivity between organizational training and workplace practice through inculcation of positive attitudinal and behavioral change among its staff. The research adopted a quasi – qualitative approach allowing for triangulation of data. Data were collected through questionnaires for lower grades and interviews for heads of section. Stratified sampling was employed to select 109 respondents who filled in the self completion questionnaires which were analyzed using the social packages for social scientists (SPSS). Eleven heads of sections were interviewed and the recorded data were analyzed using a descriptive thematic generation approach. The research findings reveal that employees are aware of the negative Human Factor issues that affected organizational culture and behavioral norms, an element which was said to be working against organizational effectiveness within the university‟s service structure and departments. Lack of good work ethics, „hunhuism‟ and absence of induction was identified as a major critical component characterizing the negative workplace practice. Additionally the study highlights cases of human factor decay as evidenced by dismissal of perpetrators. Thus, the study recommends the provision of relevant training programmes as part of Human Factor development thrust through prioritization of training programmes aimed at inculcating the correct human factor characteristics in employees